Nastroje, postawy oraz stosunek mieszkańców Grudziądza i powiatu grudziądzkiego do władzy komunistycznej w 1945 r. - Ławniczak, Remigiusz (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article describes the social moods and attitudes as well as the attitude of the inhabitants of Grudziądz and the Grudziądz poviat towards the Communist regime in 1945. From the first moments after the end of the German occupation, the population vigorously began to rebuild its socio-economic and political life. Work was undertaken in state administration and public institutions. Also prevalent at that time were anti-German attitudes, an attachment to religion, and an aversion to displaced people, among others. The inhabitants adopted a passive and expectant attitude, but were generally hostile to Communism. This was mainly due to the deepening problems of everyday life and the deeply rooted awareness of moral principles – which still had deep roots in the period of the Second Polish Republic.